Intention to Experiment With E-Cigarettes in a Cross-Sectional Survey of Undergraduate University Students in Hungary. (28th July 2016) - Pénzes, Melinda; Foley, Kristie L.; Balázs, Péter; Urbán, Róbert
ABSTRACT: Background : Electronic cigarettes are often used to promote cessation. Only a few studies have explored the motivations for e-cigarette experimentation among young adults. Objectives : The goals of this study were to assess the intention to try e-cigarettes among Hungarian university students and to develop a motivational scale to measure vulnerability to e-cigarette experimentation. Methods : 826 Hungarian university students completed an internet-based survey in 2013 to measure motives for trying e-cigarettes. We conducted exploratory factor analyses and identified factors that promote and deter experimentation. Logistic regression analysis was performed to test the concurrent predictive validity of the identified motivational factors and we used these factors to predict e-cigarette experimentation, controlling for other known correlates of e-cigarette use. Results : 24.9% of the participants have ever tried an e-cigarette and 17.2% of current nonsmokers experimented with the product. Almost 11% of respondents intended to try an e-cigarette in the future, yet only 0.6% were current e-cigarette users. Six factors were identified in the motivational scale for experimentation, four that promote usage (health benefits/smoking cessation; curiosity/taste variety; perceived social norms; convenience when smoking is prohibited) and two that deter usage (chemical hazard; danger of dependence). In a logistic regression analysis, the curiosity/taste factor was the only motivational factor significantly associated with the intention to try e-cigarettes in the future. Conclusions : This is the first study to test a motivational scale about what motivates e-cigarettes usage among university students. Additional research is needed to better understand these factors and their influence on e-cigarette uptake.